Answer:
The chosen topic is not meant for use with this type of problem. Try the examples below.
√x+2=3
−4+y=3y+4(y−3)
2+|3x|=2+3
Answer:
b = (log(y^45))/log(1/y^9) + (2 i π n)/log(1/y^9) for n element Z
Step-by-step explanation:
Solve for b:
(1/y^9)^b = y^45
Take the logarithm base 1/y^9 of both sides:
Answer: b = (log(y^45))/log(1/y^9) + (2 i π n)/log(1/y^9) for n element Z
Answer:
the answer is 6.
Step-by-step explanation:
![5^{9}/5^{6}=5^{3}](https://tex.z-dn.net/?f=5%5E%7B9%7D%2F5%5E%7B6%7D%3D5%5E%7B3%7D)